An Analysis on the Purpose of Ues, Satisfaction and Perception of Performance Outcomes of the University Information Disclosure System in Korea - et. al., Suk-Yeol Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to analyze the purposs of ues, satisfaction and perception of performance outcomes with the university information disclosure system to confirm whether it satisfies the public's right to know, and whether it provides users with customized information. The subjects of the study were 409 university professors, 175 university employees, and 102 high school teachers using the university information disclosure system. For data analysis, descriptive statistical analysis and multiple correspondence analysis were conducted on the purpose of use, satisfaction, and perception of performance outcomes of the university information disclosure system.The analysis results show, first, the overall satisfaction with the university information disclosure system is generally high. In particular, the overall satisfaction level for the purpose of'Acquiring admissions information and research evaluation' was highest at 4.05, followed by'Acquiring university information and research evaluation' at 3.97, 'Acquiringadmission information' at 3.90,'Acquiring research and evaluation information' at 3.88, and 'Acquiring university information' at 3.87, and'Acquiring university admissions and university information' at 3.56. Second, the performance perception of the university information disclosure system was also high. In particular, the'Satisfaction/fulfillment of the public’s right to know' was the highest at 4.11, followed by'Improving accountability' at 4.04 and'Providing appropriate data' at 3.84, and'Choice of university program' was lowest at 3.59. Third, the relationship between the purpose of using the university information disclosure system, satisfaction, and performance perception has been shown to have very similar levels of satisfaction. When the purpose of use was ‘Acquiring admission information’, the satisfaction and performance perceptionwas relatively low compared to other purpose of uses.